A new family of bridge functions for electrolyte solutions - Raineri, F.O.; Stell, G. (Condensed Matter Physics, 2001)
We present a new set of closures for restricted models of electrolyte solutions at the McMillan-Mayer level that improve upon the Hypernetted Chain prediction for the ion-ion pair correlation functions. The improvement is accomplished by proposing simple functional forms for the bridge functions and the specification of certain adjusting parameters according to several criteria. Under the new closures, and unlike the HNC case, the “sum” direct correlation function, which is crucial for determining the stability of the solution with respect to phase separation, remains finite at thermodynamic states along the spinodal and at the critical point.